R&D employee's intention to exchange knowledge within open innovation projects - Verena Nedon; Cornelius Herstatt (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2014)
The existing literature on open innovation strongly emphasizes on the organizational level, while neglecting the people side and especially the perspective of employees working in OIprojects. This study analyzes determinants of R&D employees' knowledge exchange in OIprojects by means of the theory of planned behavior (TPB) and a literature review regarding motivational factors influencing individuals' attitude toward knowledge exchange. An online survey amongst 133 R&D employees was conducted and data was analyzed through variancebased structural equation modeling (PLS). In our sample, subjective norm had by far the strongest impact on employees' intention to exchange their knowledge in OI-projects, although attitude and perceived behavioral control also showed highly significant and positive effects on intention. From all five identified motivational factors, enjoyment in helping was found to have the strongest influence on attitude, followed by intrinsic rewards and sense of self-worth. Extrinsic rewards and reciprocity did not show any effect on attitude.
Keywords: 330; open innovation; interorganizational cooperation; R&D partnerships; knowledge exchange; knowledge sharing; R&D employees; theory of planned behavior; TPB; motivation; structural equation modeling